Factor analysis for detection of sports talent in football players - Abrahão, Ariel (2022)
Verify the applicability of Factor Analysis - FA by crossing the variables obtained with the tests proposed by a protocol for detecting talent, anthropometry, flexibility and strength. The sample included 38 under-19 athletes from Cuiabá Esporte Clube. The evaluation consisted of the application of the iSports test protocol to detect sports talent, anthropometric tests (weight, height, BMI, WHR), flexibility test (sit and reach), manual strength test (Hand Grip) and vertical impulsion test. Through PA, 14 variables were reorganized into 4 new factors taking into account their commonalities and variances. Each new factor presents correlations between 2 or more variables that were discussed later. This type of multivariate statistical analysis proved to be efficient for grouping of data and for the possibility of being applied as a tool that helps and seeks to contemplate the multidimensionality of the identification of sporting talents.